Status of crop raiding caused by wild animals in Lansdowne forest division, Uttarakhand - RATHI, ROBIN; SINGH, AMAR; BHATT, DINESH (The Indian Journal of Agricultural Sciences, 2020)
The human-wildlife conflict is one of the serious problems faced by people living in forest fringe villages. This has been a major problem since ages especially for the people residing near the wildlife protected areas but the problem has aggravated over the period of time. After the mid 19th century, it is being considered as a major problem, affecting the social, economic and cultural life of the people especially in the Himalayan region of our country. The aim of our study was to access crop damage by the wild animals in the agricultural areas of Lansdowne forest division of Pauri district of Uttarakhand. Crop damage by the wild animals was found in almost all the study sites (ranges) during the study period.